Temperature effect on chicken egg shell investigated by XRD, TGA and FTIR - K. Naemchan (2018)
The chicken egg shell powders were annealed in air at the temperature range of 200-900°C for 4 h. The crystal structures were analyzed by x-ray diffraction (XRD), thermogravimetric analysis (TGA) and fourier transform infrared (FTIR). The natural phase was identified as calcite and no other crystalline species were detected in the annealing temperature range from room temperature up to 600°C. It was observed that the XRD peaks of calcite phase decreased and the new XRD peaks of CaO appeared after the chicken egg shells were annealed above 700 °C. At 900 °C, the chicken egg shells become porous, fragile and very white in color. CaO from the chicken egg shell was very sensitive to humidity and it was transformed to portlandite. The effects of heat treatment on the structure of chicken egg shell were carefully studied by Rietveld refinement method. TGA was used to monitor structural, thermal decompositions and phase transition from calcite to CaO. The FTIR spectra of chicken egg shell show that the relative intensities of CO32-absorption bands at the annealing temperature to that of room temperature increased. The OH absorption bands were observed at the annealing temperatures from 700-900°C. The results show that CaO obtained from chicken egg shell can be used as a moisture absorber for commercial application. © 2008 Trans Tech Publications, Switzerland.